COMPARISON OF COMBINED TRICHLOROACETIC ACID PEEL AND TOPICAL ASCORBIC ACID VERSUS TRICHLOROACETIC ACID PEEL ALONE IN THE TREATMENT OF MELASMA (Journal of Medical & Health Sciences Review, 2025)
OBJECTIVE: To compare the mean Melasma Area and Sensitivity Index (MASI) score of combined trichloroacetic acid peel and topical ascorbic acid versus trichloroacetic acid peel alone in the treatment of melasma.MATERIALS AND METHODS: Randomized Controlled Trial study conducted at Department of Dermatology, Combined Military Hospital Multan with 6-months duration. Sample sizewas taken with OpenEpi software through formula for mean difference is used to calculate sample size. Where, Mean MASI score 12-weeks after TCA & ascorbic acid treatment = 9.50±5.31, Mean MASI score 12-weeks after TCA only treatment = 15.10±4.44, Power of the study = 80%, Confidence level = 95%. Sample size was60 (30 in each group).Non-probability consecutive sampling technique was used. Patients aged 20 – 50 years, either male or female gender and diagnosed with Melasma, ≥ 3-months were included.Data analysis was done through SPSS version 23. MASI-score between the two groups was compared using independent sample t-test. Post-stratification independent sample t-test was applied and p value ≤0.05 was taken as statistically significant.RESULTS:A paired t-test was performed to compare the MASI score reduction within each group, and an independent t-test was applied to compare reductions between groups. The results indicate a significantly greater improvement in Group A (p < 0.001).Group A showed a greater reduction in MASI scores (48.1%) compared to Group B (15.6%).The treatment effect was significant across all Fitzpatrick skin types.The addition of ascorbic acid to TCA peel resulted in superior improvement in melasma treatment. These findings suggest that combining TCA peel with topical ascorbic acid significantly enhances treatment outcomes compared to TCA peel alone.CONCLUSION: Our study confirms that the combination of TCA peel and topical ascorbic acid is significantly more effective in treating melasma compared to TCA peel alone. These findings support the routine use of combination therapy for improved patient outcomes.